Leveraging Military Diplomacy in Nepal’s Foreign Policy - Maharjan, Ratna Keshari (Unity Journal, 2023)
Military diplomacy, which notably developed following the end of World War II, is the peaceful utilization of military resources for cooperative relations with foreign countries to enhance national interests and attain objectives of foreign policy. Before and after the codification of the Foreign Policy, 2020, Nepal employed a variety of diplomatic strategies. However, since military diplomacy is not explicitly incorporated into the foreign policy, this paper focuses on prevailing legislations regulating military diplomacy and the challenges they impose on relevant authorities to facilitate military diplomacy. This paper also makes recommendations to the concerned authorities to expand military diplomacy by mitigating misconceptions, taking initiatives to lead in the UN Peacekeeping Missions, establishing proper coordination, and developing common consensus about national interests in global forums. The paper uses both primary and secondary sources for data collection and desk reviews and Key Informants Interview form the foundation of the study. This paper is divided into four parts explaining the meaning and forms of military diplomacy and foreign policy, the historical aspect of military diplomacy, its use as a tool, and hindrances in promoting military diplomacy to attain objectives of foreign policy.